Lectures on Bright's Disease - Saundby, Robert, 1849-1918 (John Wright & Co., 1889)
Lectures on Bright's Disease presents a clinical and pathological study of Bright's disease. This book provides a collection of lectures pertinent to Bright's disease, including febrile, obstructive, and lithemic nephritis. Organized into three sections encompassing 15 chapters, this book begins with an overview of the presence of an albuminous body in the urine that is coagulated by heat or precipitated by neutralization. This text then discusses the significant components of dropsy, which is the most striking symptom of Bright's disease. Other chapters consider the discovery of tube casts in.